Ecologia da germinação e potencial alelopático de capim-annoni-2 (Eragrostis plana Nees) - Bittencourt, Henrique von Hertwig (2017)
The invasiveness of South African lovegrass in agroecosystems has been attributed to its biological characteristics and the ecological relations. The ecology of species germination and allelopathic interaction are poorly understood. The objective of this work was to determine the influence of environmental factors on germination, phytotoxicity of South African lovegrass extracts, to identify and quantify phenolic allelochemicals present in their fractions, to determine the influence of phytomass and soil degradation on the phytotoxicity of the aqueous extract, to monitor the degradation of the compounds present in the extracts and to identify and quantify allelochemicals in a infested soil. Experiments were carried out in the laboratory using materials collected in the field. Seeds germinated at constant temperatures of 15 to 40 ° C, but the percentages of germination were greater than 94 % only at alternating temperatures. Exposure to light increased the frequency of normal seedlings. Germination increased with increasing water potential and the number of normal plants decreased with increasing sodium chloride concentration. The highest emergence rate was observed with the seeds placed on the soil surface, whereas no emergence occurred at 4 cm. A total of nine phenolic compounds with allelochemical potential were identified in the fractions of extracts of South African lovegrass: caffeic acid, coumaric acid, ferulic acid, gallic acid, vanillic acid, catechin, epicatechin, resveratrol and rutin. The general decreasing order of general phytotoxicity of crude extracts in the development of wheat and alfalfa seedlings was ethyl, methanolic, aqueous and hexane acetate. An inversely proportional correlation was identified between vanillic acid concentration and root and total alfalfa seedlings length. The simulation of phytomass and soil degradation caused an increase in the phytotoxicity of the extracts on germination and seedling development, proving the release of the allelochemicals and the influence of the soil in the increase of its phytotoxicity. The ether extracts of the straw and soil showed changes in their chromatograms from the first to the seventh day of incubation, while the mixture of straw + soil showed greater changes only between the first and third day of degradation. Four phenolic compounds with allelochemical potential were identified in the South African lovegrass infested soil: coumaric acid, ferulic acid, catechin and epicatechin. The concentration of these compounds was higher at the soil surface and horizontally near the South African lovegrass plants, showing an association between concentrations of allelochemicals and plant distance.